(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The course of pregnancy and childbirth in pregnant women with hepatitis B is still considered an urgent issue in obstetrics and gynecology. Pregnant women with hepatitis B often experience complications such as threatening miscarriage, premature birth, premature rupture of the membranes, bleeding during childbirth and in the early postpartum period. The most basic and highest risk is vertical transmission.